The silent war [compact disc, unabridged] - Bova, Ben, 1932-2020 (Bova, Ben, 1932-2020- Asteroid wars, 2005)
The lives of thousands hang in the balance when the ruthless competition between Astro Corporation and Humphries Space Systems reaches a peak and others decide to take advantage of the conflict.